Analysis of the use of educational materials by radiologists and radiology residents in Brazil: paradigm shift - Chojniak,Letícia Motono (2022)
Abstract Objective: To profile the use of educational materials by radiologists and radiology residents in Brazil. Materials and Methods: This was a cross-sectional, descriptive, observational study in which an electronic questionnaire was sent via email to physicians working in the field of radiology. The questionnaire contained questions regarding the profile, education, and place of work of the physicians, as well as their access to educational resources and the types of educational materials they used most. Results: The questionnaire was completed by 265 physicians. The mean age of the respondents was 38.2 years. Of the 265 respondents, 212 (80.0%) worked with ultrasound, 206 (77.7%) worked with computed tomography, 170 (64.2%) were board-certified, 166 (62.6%) were male, 174 (65.7%) worked at private facilities, and 167 (63.0%) had no academic affiliation. The mean weekly total study time was 9.6 h (median, 6 h), being higher among physicians in training, among those who worked at public facilities, and among those who worked at teaching hospitals. Regarding the device employed in order to access educational materials, there was a trend toward greater use of computers, which were employed by 65.3%. The majority of the respondents (61.9%) chose to access educational materials that were free of charge, the most common sources being websites, eBooks, and online journals. Conclusion: Electronic and digital resources are the main means of access to educational materials used by radiologists in Brazil, the most commonly used resources being web sites, eBooks, and online journals.